Impact of irradiance and inorganic carbon availability on heterologous sucrose production in Synechococcus elongatus PCC 7942 - Yun, Lisa; Zegarac, Robert; Ducat, Daniel C. (Frontiers in Plant Science, 2024)
Cyanobacteria have been proposed as a potential alternative carbohydrate feedstock and multiple species have been successfully engineered to secrete fermentable sugars. To date, the most productive cyanobacterial strains are those designed to secrete sucrose, yet there exist considerable differences in reported productivities across different model species and laboratories. In this study, we investigate how cultivation conditions (specifically, irradiance, CO2, and cultivator type) affect the productivity of sucrose-secreting Synechococcus elongatus PCC 7942. We find that S. elongatus produces the highest sucrose yield in irradiances far greater than what is often experimentally utilized, and that high light intensities are tolerated by S. elongatus, especially under higher density cultivation where turbidity may attenuate the effective light experienced in the culture. By increasing light and inorganic carbon availability, S. elongatus cscB/sps produced a total of 3.8 g L-1 of sucrose and the highest productivity within that period being 47.8 mg L-1 h-1. This study provides quantitative description of the impact of culture conditions on cyanobacteria-derived sucrose that may assist to standardize cross-laboratory comparisons and demonstrates a significant capacity to improve productivity via optimizing cultivation conditions.